Solar cell with coating
By coating the ta-C layer on the outer surface of the perovskite solar cell, the instability problem of perovskite solar cell to moisture and air is solved, achieving longer life and higher stability.
Patent Information
- Application Number
- CN202380062926.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-03
- Filing Date
- 2023-11-03
- Publication Date
- 2025-03-28
AI Technical Summary
The impact of perovskite solar cells on moisture and air is unstable, resulting in external stability problems.
The outer surface of the perovskite solar cell is coated with a layer containing ta-C, which reduces the ingress of water and air using the sealing effect of ta-C, thereby improving stability.
Through the use of ta-C coating, the stability of solar cells is significantly improved, its life span is extended, and high power conversion efficiency is maintained in high humidity environments.
Smart Images

Figure CN119732214A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a solar cell with a coating and a method for producing such a solar cell with a coating. Background Art
[0002] Solar cells collect light energy and convert it directly into electrical energy, with three basic properties, namely light absorption, separation of charge carriers, and individual extraction of carriers. Solar cells are typically mounted on and / or contained in a layered support structure, the resulting entity being called a module (sometimes also called a solar cell, although the solar cell is its internal component), which is typically a sealed unit that can then be described as an encapsulated solar cell. Multiple solar cell modules connected together constitute a solar module, which is typically sealed in a protective housing. Multiple solar modules connected together constitute a solar panel. Solar panels amplify and direct the energy generated from individual solar cells.
[0003] Many types of solar cells are known and widely used. However, a common problem with solar cells is their lifetime. To improve economic efficiency, a longer lifetime is desired. Many solar cells are exposed to harsh environments, wind, UV rays and / or weather (especially rain), resulting in wear damage.
[0004] US 2009 / 0252894 A1 describes the use of silicon and oxygen-containing barrier coatings, for example 500 nm thick, to protect moisture-sensitive LED devices.
[0005] WO 2009 / 098241 A1 describes the need to hermetically seal solar cells to protect them from external conditions, such as moisture.
[0006] US2020 / 0013974A1 describes a solar cell including a photoelectric conversion layer containing perovskite, and a method for producing the solar cell. However, it does not consider the problem of solar cells being exposed to moisture and how to prevent moisture.
[0007] One particular type of solar cell has a light-harvesting active layer that includes a perovskite structured material.
[0008] However, a drawback of perovskite solar cells and other solar cells to varying degrees is their lack of intrinsic and extrinsic stability. In recent years, the intrinsic stability problem of solar cells, especially perovskite solar cells, has been alleviated using strategies such as compositional engineering, doping, and incorporation of two-dimensional perovskites.
[0009] However, extrinsic instabilities remain a major problem for solar cells, especially perovskite solar cells. They are unstable to environmental influences such as water and oxygen, as well as other influences such as thermal stress, light influence and mechanical brittleness.
[0010] It is an object of the present invention to solve and preferably improve the identified stability problems of solar cells, in particular the extrinsic stability problems.It is an object of specific embodiments to provide solar cells with improved stability to water damage and / or air damage. Summary of the invention
[0011] Therefore, the present invention provides a solar cell assembly, comprising:
[0012] adjacent layers defining an inner cavity,
[0013] a sealant between adjacent layers to seal the inner cavity, and
[0014] The solar cell in the sealed cavity,
[0015] The invention is characterized in that a layer containing ta-C is coated on the outer surface of the component, and the solar cell is a perovskite solar cell.
[0016] The solar cell module of the present invention can be prepared by a method comprising:
[0017] (i) providing adjacent layers, such as a front layer and a back layer, which define an inner cavity when the adjacent layers are sealed together,
[0018] (ii) providing a solar cell between the layers, wherein the solar cell is a perovskite solar cell.
[0019] (iii) positioning a sealant between the layers to seal the layers together and form a sealed interior cavity containing the solar cell,
[0020] (iv) Applying a layer comprising ta-C to the outer surface of the component.
[0021] It was found that the solar cell modules of the present invention exhibit improved stability as shown in the following examples. DETAILED DESCRIPTION
[0022] Therefore, the solar cell module of the present invention comprises:
[0023] adjacent layers defining an inner cavity,
[0024] a sealant between adjacent layers to seal the inner cavity, and
[0025] The solar cell in the sealed cavity,
[0026] The outer surface of the component is coated with a layer comprising ta-C, and the solar cell is a perovskite solar cell.
[0027] The sealing effect of the ta-C coating is used to achieve reduced ingress of water and / or air / oxygen, thereby improving stability.
[0028] Typically, the ta-C-containing coating is present on one or more adjacent layers and / or a sealant.
[0029] The coating comprising ta-C may be on the backside layer, on the frontside layer or on both of the components.
[0030] Optionally, the sealant comprises ta-C or comprises a coating comprising ta-C.
[0031] Preferably, the assembly is characterized in that a coating comprising ta-C is present at the joint between the sealant and each adjacent layer. The sealing result is improved by using ta-C at joints where the ingress of water and / or air / oxygen may be a particular problem.
[0032] In addition to ta-C coated on the sealant or part thereof, other surfaces of the solar cell component can be ta-C coated. For example, the front layer of the component can include a coating of ta-C, preferably at least on the outer surface of the front layer. In a typical method of manufacturing the component, the substrate layer is pre-coated with ta-C before being formed into a solar cell component. Therefore, in addition to the ta-C on the sealant between the layers, the front component layer and / or the back component layer can be coated on the outer surface with ta-C. In order to apply the sealant, the edges of the front layer and the back layer are appropriately coated.
[0033] In the coating method, ta-C is applied to the component in the coating chamber. The ta-C coating can be applied to and thus covers all of the front layer outer edges, the back layer outer edges, and the sealant. In other words, ta-C can coat substantially the entire side of the component, achieving the intended purpose of coating the sealant and the joints between the front and back layers.
[0034] In some embodiments, all backside layers, frontside layers, and sealants are coated with a coating comprising ta-C.
[0035] Therefore, the adjacent layers of the preferred assembly are the front layer (also referred to as the lower layer and shown as the lower layer in the accompanying drawings) and the back layer (also referred to as the upper layer and shown as the upper layer in the accompanying drawings). The front layer can be a substrate to which the solar cell is attached and / or on which the solar cell has been formed, or a substrate comprising a solar cell attached and / or on which the solar cell has been formed. The back layer may also comprise an electrode. As described in the following embodiments, the solar cell can be made in situ on, for example, a glass substrate (or layer) and then encapsulated in the front layer and the back layer. The result is that a cavity is formed and sealed between the layers, the cavity typically comprising an air gap and the solar cell. It will be understood that the air gap is typically very small. However, the present invention solves the problem of water and / or moisture entering this gap.
[0036] In the solar cell assembly of the present invention, light enters the active components of the solar cell through the front layer and / or the back layer. The front layer is suitably made of or comprises a transparent material. Another option is that both the front layer and the back layer are made of or comprise a transparent material. In an embodiment of the present invention, the transparent material is glass, epoxy resin or polymer.
[0037] Photovoltaic (PV) glass is commonly used to encapsulate individual photovoltaic solar cells. PV glass can be used because it is highly transparent, durable, and stable under solar radiation. The glass is separate from the solar cell, and the glass is added to protect the solar cell, but also becomes a functional component of the solar module.
[0038] In a specific embodiment of the invention, the solar cell comprises soda-lime-silica (SLS) glass. Borosilicates can also be used for PV glass. Other PV glass substitutes can also be used - such as organic glass / acrylic glass or tempered glass. These substitutes can reduce the light transmittance through the solar cell module, thereby reducing the power conversion efficiency of the solar cell, but they do provide more protection from environmental influences.
[0039] Alternatively, a transparent polymer can be used alone or in combination with glass. For example, materials such as epoxy resin, TPU and PET can be used to replace glass.
[0040] Preferably, all outer surfaces of the component comprise a coating comprising ta-C. In a specific embodiment of the invention, the component is an encapsulated solar cell, all outer surfaces of which comprise a coating comprising ta-C.
[0041] The components of the solar cell assembly / module are sealed together. Sealants are conventional in the manufacture of solar cells and the present invention is generally applicable to all such useful sealants. Suitable sealants include epoxy resins, ethylene vinyl acetate, ionomer polymers (e.g., polyethylene ionomers such as Surlyn ® ), polydimethylsiloxane, poly(methyl methacrylate) (PMMA), thermoplastic polyurethane (TPU), polyisobutylene and any mixture thereof. Fluoropolymers (e.g., PTFE), polyethylene terephthalate, poly(vinyl alcohol-co-ethylene) (poly (vinyl alconol-co-ethylene, EVOH), paraffin wax, organosiloxane, silicone resin or any mixture thereof may also be used as a sealant. Epoxy resin is a preferred sealant and is used in the following examples.
[0042] Epoxy resins are well known in the art as high strength sealants with impressive core toughness. Compared to other sealants, they provide improved protection and have improved resistance to environmental / chemical influences. To date, the sealing properties of epoxy resins have been considered satisfactory. Epoxy resins or their interfaces with solar cell components (e.g., glass layers, substrates, etc.) have not yet been identified as factors causing solar cell stability problems. A feature of the present invention is the identification of the problem that sealants (usually but not always epoxy resins) used for solar cells have unacceptable barrier properties (especially to oxygen and moisture) and / or there is unacceptable sealing at the connection between the sealant (usually epoxy resin-based) and the solar cell layer (e.g., glass).
[0043] In a preferred embodiment, the ta-C-containing coating consists of ta-C.
[0044] The ta-C coating may typically have various thicknesses. The layer comprising ta-C typically has a thickness of 0.3 nm or more or 0.5 nm or more. It will be appreciated that above certain thicknesses, further improved sealing is rarely achieved or almost absent. Typically, the thickness is at most 200 nm, suitably at most 100 nm, more typically at most 75 nm or at most 50 nm. Typically, the thickness is 1 nm to 50 nm. In a preferred embodiment, the thickness is 5 nm to 20 nm or 5 nm to 10 nm. Typically, the ta-C coating is applied directly to the solar cell module. For coatings of increased thickness (e.g., above 50 nm), it is optional to deposit a seed layer onto the module and then deposit the ta-C layer. There may be a thin seed layer (e.g., Ti, Cr, NiCr, Ni, Si) between the module and the ta-C coating, which may allow a thicker ta-C coating to exist and avoid delamination.
[0045] Perovskite solar cells are solar cells that use perovskite-structured compounds (referring to a specific crystal structure) as light-collecting active layers. Perovskite is a crystal structure that usually has the formula ABX3, where X is an anion, and A and B are both organic cations or inorganic cations. Perovskite structure materials are usually hybrid organic / inorganic and halide-based. Examples of A include Cs, methylammonium (MA) and formamidinium (FA); examples of B include Pb and Sn. A and B are respectively 1 and 2, and each has a valence of 1. + and valence is 2 + The cation X is a cation with a valence of 1. - halide anions (e.g. I, Br, Cl). Commonly used perovskite materials include MAPbI3, FAPbI3, CsPbI3 and MA x FA (1-x) PbI3. There are also various other mixed cation / anion compositions in which various ratios of cations and anions are used.
[0046] Perovskites are typically placed between two electrodes that are connected to an external circuit. There may be layers between the perovskite and the electrodes that allow specific charges to be drawn out. In some cells, these layers are hole transport layers and electron transport layers. Materials used for the hole transport layer include metal oxides (e.g., NiO, Cu2O, CuGaO2), metal sulfides, metal oxysulfides, and / or organic materials (e.g., P3HT, PTAA, and PEDOT:PSS). The electron transport layer can be made of materials such as PCBM, C60, TiO2, and SnO2. Optionally, in order to improve the contact between the top electrode and the electron transport layer, a layer containing, for example, BCP, ZnO, and Nb-TiO x The top electrode of the solar cell can be made of metals such as silver, gold, copper or aluminum. The electrode at the front (or light entry side) of the solar cell is usually made of a transparent conductive oxide such as indium tin oxide, aluminum-doped zinc oxide or fluorine-doped tin oxide.
[0047] Perovskite solar cells can be cells of pin or nip structures, sometimes referred to as inverted structures or normal structures. Typically, the cell includes a first electrode, a hole transport layer, a perovskite, an electron transport layer, and a second electrode. A pin cell includes (in order) a top electrode, an electron transport layer, a perovskite, a hole transport layer, and a front electrode. A nip cell includes (in order) a top electrode, a hole transport layer, a perovskite, an electron transport layer, and a front electrode. The sealing of the present invention is believed to be applicable to a variety of device structures and architectures.
[0048] Advantages of using perovskite solar cells include ease of production and high efficiency at low production costs. The disadvantages of stability described elsewhere are addressed in the present invention.
[0049] In a specific embodiment, an encapsulated perovskite solar cell is provided, having a front and back layer made of glass and sealed using an epoxy sealant / adhesive, comprising an inner cavity between the two layers (wherein the perovskite solar cell is located), wherein the outer surface thereof is coated with a ta-C coating at a depth of 1 nm to 50 nm. In a specific example made and tested as described below, the ta-C coating was about 20 nm and gave good results.
[0050] The present invention also provides a method for making a solar cell module, wherein the solar cell is a perovskite solar cell. One such method comprises:
[0051] (i) providing adjacent layers, such as a front layer and a back layer, which define an inner cavity when the adjacent layers are sealed together,
[0052] (ii) providing solar cells between the layers,
[0053] (iii) positioning a sealant between the layers to seal the layers together and form a sealed interior cavity containing the solar cell,
[0054] (iv) Applying a layer comprising ta-C to the outer surface of the component.
[0055] The sealant is typically applied at or towards the outer edges of the layers being sealed together.The solar cells may be formed on the front side layer prior to sealing the solar cells between the layers.
[0056] These methods may suitably produce components conforming to the above-described optional and preferred features of the invention.
[0057] Amorphous carbon is a free, reactive form of carbon that has no crystalline form. There are various forms of amorphous carbon films, which are generally characterized by the hydrogen content of the film and the sp 2 :sp 3 Ratios to classify.
[0058] In the literature of this field, amorphous carbon films are divided into seven categories (see the following table, taken from the "Name Index of Carbon Coatings" of the Fraunhofer Institute for Surface Engineering and Thin Films):
[0059]
[0060] Tetrahedral hydrogen-free amorphous carbon (ta-C) is characterized by containing little or no hydrogen (less than 5 mol %, usually less than 2 mol %) and a high content of sp 3 Hybridized carbon atoms (usually more than 80% of the carbon atoms are in sp 3 state). The sp of ta-C is appropriately measured by XPS. 2 and sp 3 The ta-C density is suitably measured using SIMS or RBS (see, for example, https: / / doi.org / 10.1016 / S0257-8972(02)00247-5).
[0061] Although the term "diamond-like carbon" (DLC) is sometimes used to refer to all forms of amorphous carbon materials, the term is used herein to refer to amorphous carbon materials other than ta-C. Common methods of DLC manufacture use hydrocarbons (e.g., acetylene), thereby introducing hydrogen into the film (in contrast to ta-C films where the starting material is typically high-purity graphite that is free of hydrogen).
[0062] The ta-C coating can be deposited using known techniques such as physical vapor deposition, one of which is the cathodic vapor arc deposition method. In this method, an electric arc is used to evaporate material from a cathode target. The resulting evaporated material then condenses on the substrate to form a thin film of the coating. Cathodic arc deposition of tetrahedral amorphous carbon coatings, metallic coatings, dielectric coatings and other such coatings is known in the art and offers the potential for depositing high quality thin films.
[0063] Ta-C is a dense amorphous material described as consisting of disordered sp 3 The components are connected to each other by strong bonds, similar to those present in disordered diamond (see Neuville S, "New application perspective fortetrahedral amorphous carbon coatings", QScience Connect 2014:8, http: / / dx.doi.org / 10.5339 / connect.2014.8). Due to the structural similarity between ta-C and diamond, ta-C is also a very hard material, with hardness values typically greater than 30 GPa.
[0064] For use in the present invention, the hydrogen content of ta-C can be less than 10%, generally less than 5%, preferably less than 2% (e.g., less than 1%). The percentage of hydrogen content provided herein refers to the molar percentage (rather than the mass percentage of hydrogen). Ta-C is preferably not doped with other materials (metal or non-metal). In a preferred embodiment of the present invention, as described in detail in the examples listed below, the component is coated with substantially hydrogen-free ta-C.
[0065] It is believed that the ta-C coating used in the present invention can generally achieve improved sealing. 3 The carbon content is suitably 30% or more, more suitably 40% or more. 3 The carbon content may range from 30% to 95%. In some embodiments, the higher sp 3 The carbon content contributes to improved sealing. Typically, the sp 3 The carbon content is 50% or more. In a preferred embodiment, the sp 3 The content is 60% or more or 70% or more, even more preferably higher than 80%.
[0066] The ta-C coating of the present invention is typically deposited by filtered cathodic vacuum arc (FCVA) and / or by sputtering, and the machines and processes for both sputtering and depositing ta-C by FCVA are conventional and well known in the art, so they are not a feature of the present invention. It will be understood that these coatings are carbon coatings, preferably substantially silicon-free and oxygen-free. A suitable method and apparatus are described in WO / 2012 / 044258, and an "X-bend" system is disclosed. Another example of a suitable deposition method is described in WO2009 / 151404. Yet another example of a suitable deposition method is described in WO2020 / 187744 - specifically the use of an adhesion promoting layer is described in this application. The ta-C coating of the present invention is preferably deposited by FCVA. As will be appreciated by the skilled person, the FCVA device produces a carbon coating comprising positively charged C for depositing the ta-C coating. + Coating of ions with electron beam.
[0067] Example
[0068] The present invention will now be described in more detail with reference to the accompanying drawings, in which:
[0069] Figure 1 A schematic top view of a perovskite device stack is shown.
[0070] Figure 2 Schematic cross-sections of solar cell devices are shown, which are (a) a control of the present invention and (b)-(e) embodiments of the present invention;
[0071] Figure 3 After 6900 hours of stability testing, Figure 2 Images of three devices (i.e., control, TAC-1, and TAC-2) schematically shown in FIG.
[0072] Figure 4 Shown in Figure 2 Normalized power conversion efficiency (PCE) of the three devices (i.e., control, TAC-1, and TAC-2) schematically shown in FIG. 5 over 6900 hours.
[0073] With reference to the accompanying drawings, Figure 1 A schematic top view of a perovskite device stack is shown, which is incorporated into a solar cell with a coating according to the present invention. Figure 1 The device shown in is an inverted (pin) structured perovskite solar cell.
[0074] Figure 2 Five perovskite stack devices are shown, namely a control (prior art) and an embodiment of the invention, namely TAC-1, TAC-2, TAC-3 and TAC-4.
[0075] The control example is a conventional perovskite solar cell encapsulated with soda-lime-silicon (SLS) glass and sealed with epoxy sealant. "TAC-1" uses ordinary SLS glass for encapsulation, and then a ta-C layer is applied on the edge after sealing with epoxy resin. "TAC-2" uses ta-C coated SLS glass for the back layer, and ordinary SLS glass for encapsulation on the front layer, and the ta-C layer is applied on the edge after sealing with epoxy resin. "TAC-3" uses ta-C coated SLS glass for both the front and back layers, and the ta-C layer is applied on the edge after sealing with epoxy resin. "TAC-4" uses ta-C coated SLS glass for the back layer, and ordinary SLS glass for encapsulation on the front layer, and epoxy resin is used to seal.
[0076] The perovskite solar cell devices used in the experiment were made of the following materials:
[0077] Hole transport layer: Nickel oxide (NiO x )
[0078] Perovskite layer: Tri-cation perovskite (Cs 0.05 (MA 0.17 FA 0.83 ) 0.95Pb(I 0.83 Br 0.17 )3)
[0079] Electron transport layer: phenyl-C61-butyric acid methyl ester (PCBM)
[0080] Buffer layer (thin layer between PCBM and Ag): Bathocuproine (BCP)
[0081] Electrode: Ag.
[0082] The thickness of the nickel oxide layer is about 50 nm, the thickness of the perovskite layer is in the range of 300 nm to 500 nm, the thickness of the PCBM layer is about 50 nm, the thickness of the BCP layer is 5 nm, and the thickness of the Ag electrode is 80 nm to 100 nm.
[0083] The thickness of the SLS glass is 1 mm, and the SLS glass is placed directly on the Ag electrode. The thin film stack is deposited directly on the fluoride-doped tin oxide (FTO) glass substrate. For clarity, FTO glass refers to SLS glass coated with a FTO film layer.
[0084] Figure 3 The stability test results of three of these devices, namely the control, TAC-1 and TAC-2, are shown. The results show that the control device shows maximum degradation after 6900 hours, while the ta-C coated devices, TAC-1 and TAC-2, are still visually intact.
[0085] Figure 4 The stability test results for the same three devices are shown graphically. Each data point on the graph corresponds to the average PCE of a range of 3 to 6 devices. It shows that the control device shows the greatest degradation, while after 6900 hours at 50% relative humidity and 20°C, the ta-C coated devices TAC-1 and TAC-2 have not yet reached their T in the measured time frame. 80 Lifespan (T 80 is the time required for the PCE to decrease by 20% from the initial value). In addition, these devices show T 95 The lifetime (the time required for PCE to decrease by 5%) is 28 and 34 times that of the control, respectively. 95 The lifetime is 127 hours, while the T 95 The lifetimes were 3614 hours and 4351 hours, respectively. Thus, the solar cells treated according to the present invention exhibit improved stability.
[0086] In more detail, perovskite solar cells are fabricated on fluoride-doped tin oxide (FTO) substrates. The etched FTO substrates are cleaned in a soapy water and ethanol bath, then air-dried and treated in a UV ozone chamber to make their surface more hydrophilic. The cleaned FTO substrates are then coated with a hole transport layer. The organic-inorganic hybrid perovskite layer is deposited using an anti-solvent-assisted method in an inert atmosphere. The film is then annealed at a temperature between 100°C and 135°C. Subsequently, a spin coating method is used to deposit the electron transport layer. The film is then annealed at the decomposition temperature of the perovskite to obtain a dense film. Afterwards, a buffer layer is deposited to improve the contact between the electrode and the electron transport layer. Finally, 100nm thick electrodes made by thermal evaporation of metals such as silver, gold, copper, and aluminum are used to complete the device fabrication.
[0087] The edges of the perovskite device stack are then cleaned to provide space for the encapsulant before starting the epoxy encapsulation process. The soda-lime-silica glass is cut to the required size and edge encapsulated / sealed using an organic encapsulant. An edge encapsulant (sealant) is applied to the edges of the perovskite device stack to connect it to the device, which is then dried at 60°C to 90°C for 10 minutes to form a mechanically strong encapsulation.
[0088] Finally, the ta-C layer (depth of about 20nm, sp 3 Content is about 80%) is deposited on the edge of the device, covering the sealant and the connection between the sealant and the front device layer and the back device layer to protect the device from moisture and oxygen.
[0089] For TAC-2, the glass substrate is first coated with a plasma beam substantially perpendicular to the glass plate, the plasma beam containing positively charged carbon ions. The thickness of the ta-C coating on the glass substrate is 5nm. The ta-C coated glass is then cut into the required size and connected to the perovskite cell stack. The mask is then placed on the top and bottom glass surfaces, and then the side surfaces of the solar cell device are coated with ta-C without applying any substrate bias. The ta-C coating on the glass surface remains thin enough to ensure that it is transparent. As with other test devices, the ta-C coating on the edge is 20nm.
[0090] Of course, the coating on the edge can be thicker as it does not need to be transparent, for example the coating on the edge can have a thickness of 100nm or more to enhance functionality. However, thicker coatings increase cost and production time. For thicker ta-C coatings on edge surfaces, a seed layer is often used to improve the adhesion of the ta-C.
[0091] Therefore, the present invention provides ta-C coated solar cells and methods and apparatus therefor.
Claims
1. A solar cell assembly, comprising: adjacent layers defining an inner cavity, a sealant between the adjacent layers to seal the inner cavity, and Solar cells in a sealed cavity, The invention is characterized in that a layer containing ta-C is coated on the outer surface of the component, and the solar cell is a perovskite solar cell. 2 . The solar cell component according to claim 1 , wherein a coating comprising ta-C is present on one or more of the adjacent layers and / or on the encapsulant.
3. The solar cell module according to claim 1 or claim 2, wherein a coating comprising ta-C is present at the connection between the encapsulant and each of the adjacent layers.
4. A solar cell component according to any one of claims 1 to 3, wherein adjacent layers of the component are a front layer and a back layer, wherein the front layer is a substrate to which solar cells are attached and / or a substrate on which solar cells have been formed, or the front layer includes a substrate to which solar cells are attached and / or a substrate on which solar cells have been formed.
5. The solar cell module according to claim 4, wherein the back side layer of the module comprises a coating of ta-C.
6. The solar cell module according to claim 4 or claim 5, wherein the coating comprising ta-C covers all of the front layer outer edges, the back layer outer edges and the sealant.
7. The solar cell module according to any of the preceding claims, wherein the front layer and optionally the back layer are made of or comprise a transparent material such as glass, epoxy resin or polymer.
8. The solar cell module according to claim 7, wherein the transparent material is glass (eg soda-lime-silica glass).
9. The solar cell module according to any of the preceding claims, wherein the encapsulant is selected from epoxy resins, ethylene vinyl acetate, epoxy resins, polyethylene ionomers, polydimethylsiloxanes, poly(methyl methacrylate) (PMMA), thermoplastic polyurethanes (TPU), polyisobutylenes, fluoropolymers (e.g. PTFE), polyethylene terephthalate, poly(vinyl alcohol-co-ethylene) (EVOH), paraffin waxes, organosiloxanes, silicone resins or any mixtures thereof.
10. The solar cell module according to claim 9, wherein the sealant is an epoxy resin.
11. The solar cell component according to any one of the preceding claims, comprising two electrodes, a hole transport layer, an electron transport layer and a perovskite.
12. The solar cell assembly according to claim 11, wherein the hole transport layer comprises a metal oxide (e.g., NiO, Cu2O, CuGaO2), a metal sulfide, a metal oxysulfide and / or an organic material such as P3HT, PTAA and PEDOT:PSS, and the electron transport layer comprises PCBM, C60, TiO2 or SnO2.
13. The solar cell module according to any one of the preceding claims, wherein the sp of the ta-C 3 The carbon content is more than 50%. 14 . The solar cell component according to claim 1 , wherein the ta-C-containing layer has a thickness of 1 nm to 100 nm.
15. The solar cell component according to any of the preceding claims, wherein the component is an encapsulated solar cell and all of its outer surfaces comprise a coating comprising ta-C.
16. The solar cell module according to claim 15, comprising a first electrode, a hole transport layer, a perovskite, an electron transport layer, and a second electrode, wherein the thickness of the coating layer comprising ta-C is at most 50 nm, the sp 3 The carbon content is more than 70%.
17. A method for manufacturing a solar cell module according to any one of the preceding claims, comprising: (i) providing adjacent layers, such as a front layer and a back layer, which define an inner cavity when the adjacent layers are sealed together, (ii) providing a perovskite solar cell between said layers, (iii) positioning a sealant between the layers to seal the layers together and form a sealed interior cavity containing the solar cell, (iv) Applying a layer comprising ta-C to the outer surface of the component.
Citation Information
Patent Citations
Moisture barrier coatings for organic light emitting diode devices
US20090252894A1
Solar cell and method for producing same
US20200013974A1
A novel coating having reduced stress and a method of depositing the coating on a substrate
WO2009151404A1
Filter for removing macro-particles from a plasma beam
WO2012044258A1
Improved coating processes
WO2020187744A1